Perbedaan Produksi Air Susu Ibu (ASI) Sebelum dan Sesudah Pemberian Pijat Oketani pada Ibu Menyusui - Ni Kadek Rina Purnami; Ni Nyoman Budiani; Asep Arifin Senjaya (ProHealth Journal, 2026)
Breastfeeding is a crucial process for the growth and development of infants, yet it is not uncommon for mothers to experience difficulties in producing sufficient breast milk. This study aims to analyze the differences in breast milk production before and after applying Oketani massage in breastfeeding mothers at the Independent Practice Location of Midwife Made Sri Devi Indrawati, S. Keb., Bd. The study used a pre-experimental pretest posttest one group design and an observational method with a quantitative approach. The intervention was carried out once a day for 15-20 minutes for 3 consecutive days. The respondents consisted of 20 breastfeeding mothers with diverse characteristics regarding age, education, occupation. The results showed that before the Oketani massage, 45% of mothers had insufficient breast milk production, and 55% had adequate production. In contrast, 55% had abundant production after the massage, 40% had adequate production, and only 5% had insufficient production. The Wilcoxon statistical test indicated a significant difference with a p-value of 0.000 < 0.05, meaning that breast milk production before and after the Oketani massage showed a significant difference. Oketani massage can be an effective alternative in increasing breast milk production, especially for mothers who struggle to produce sufficient breast milk. It is concluded that Oketani massage is effective in increasing breast milk production in breastfeeding mothers. It is recommended that midwives educate breastfeeding mothers on Oketani massage so that they can try this technique with professional assistance and so that future researchers can conduct comparative studies with a control group.